2018
DOI: 10.1097/pai.0000000000000460
|View full text |Cite
|
Sign up to set email alerts
|

The Usefulness of Phospholipase A2 Receptor and IgG4 Detection in Differentiation Primary Membranous Nephropathy From Secondary Membranous Nephropathy in Renal Biopsy

Abstract: Membranous nephropathy (MGN) is the most common cause of the nephrotic syndrome in adults. Most cases of MGN are primary, but secondary MGN are frequently encountered. Determination of secondary MGN is crucial for initiation of appropriate treatment. The diagnostic performance of the phospholipase A2 receptor (PLA2R) and immunoglobulin G4 (IgG4) detection based on immunohistochemistry were evaluated using biopsy tissues of 59 primary and 56 secondary MGN cases for discrimination between primary MGN and seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…Based on our results, IHC determination of PLA2R and IgG4 can be associated with improved diagnostic accuracy of primary MN. This is in line with other clinical studies which opined that high expression of IgG4 in patients with idiopathic MN occur in addition to increased expression of PLA2R in renal samples of these patients and may lead to enhance differential power of detection primary and secondary MN [20,26,34].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Based on our results, IHC determination of PLA2R and IgG4 can be associated with improved diagnostic accuracy of primary MN. This is in line with other clinical studies which opined that high expression of IgG4 in patients with idiopathic MN occur in addition to increased expression of PLA2R in renal samples of these patients and may lead to enhance differential power of detection primary and secondary MN [20,26,34].…”
Section: Discussionsupporting
confidence: 91%
“…As indicated by Yeo et al, primary MN can be distinguished from secondary forms through immunohistochemical detection of PLA2R and IgG4 deposits from renal biopsy with acceptable sensitivity and specificity of the test. Simultaneous positivity rates for PLA2R and IgG4 demonstrated an increased specificity in case of primary MN detection [26]. IHC staining has previously been shown to be the most sensitive technique, identifying MN patients correlated with anti-PLA2R antibodies [27].…”
Section: Discussionmentioning
confidence: 99%
“…Five of ten cases tested (50%) demonstrated positive PLA2R staining in the glomerular capillary walls (5/10). Evaluation of IgG subclasses (IgG1-G4) revealed that these PLA2R+ membranous deposits were IgG4 dominant (or codominant), as has been previously described in primary/idiopathic MN [23]. Although serum data was only available in three patients, all with tissuepositivity for PLA2R, only one patient had elevated serum anti-PLA2R antibodies at the time of testing.…”
Section: Discussionsupporting
confidence: 58%
“…Further studies are needed to discover if the prevalence of anti-PLA2R antibodies is affected by ethnicity or other unknown factors. In a study by Yeo et al [ 26 ], histologic detection of PLA2R showed a sensitivity of 83% and a specificity of 88% in identifying primary MN, and a meta-analysis including about 600 patients with MN showed similar results. Detection of PLA2R in glomeruli and anti-PLA2R antibodies in serum is expected to be more sensitive and specific in discriminating between primary and secondary MN.…”
Section: Discussionmentioning
confidence: 83%